Development of Antibodies against Chondroitin Sulfate A-Adherent Plasmodium falciparum in Pregnant Women - Maubert, Bertrand (American Society for Microbiology, 1999)
In areas where Plasmodium falciparum is endemic, pregnant women are at increased risk for malaria, and this risk is greatest during the first pregnancy. The placenta sequesters parasites that are able to cytoadhere to chondroitin sulfate A (CSA), a molecule expressed by the placental syncytiotrophoblast, while parasites from a nonpregnant host do not bind to CSA. Cytoadherence is mediated by the expression of variants of the P. falciparum-erythrocyte membrane protein 1 family. Each member of this molecule family induces antibodies that specifically agglutinate infected erythrocytes and inhibit their cytoadherence ability. We investigated whether the higher susceptibility of primigravidae was related to the lack of immune response towards CSA-binding parasites. In a cross-sectional study, primigravidae delivering with a noninfected placenta were less likely to have antibodies agglutinating CSA-binding parasites than multigravidae (P < 0.01). In contrast, parasites from nonpregnant hosts were as likely to be recognized by the sera from women of various parities. In a longitudinal study, at 6 months of pregnancy, antibodies against CSA-binding parasites were present in 31.8% of primigravidae and in 76.9% of secundigravidae (P = 0.02). The antibodies against CSA-binding parasites inhibited the cytoadherence of a CSA-adherent parasite strain to the human placental trophoblast. Our data support the idea that the higher susceptibility of primiparae is related to a lack of a specific immune response to placental parasites.